2009
DOI: 10.1109/tmtt.2009.2017317
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based RFID-Enabled Wireless Platforms for Sensing Applications

Abstract: Abstract-In this paper, the feasibility of inkjet printing of circuit and microwave structures on paper-based substrates is investigated for the first time in the implementation of a complete low-cost wireless platform for sensors. First, the system-level design of the module including the amplifier characterization were carried out to ensure optimum performance of the sensor modules in the UHF bands used in RF identification communication. These results were then used to design two different antenna structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(54 citation statements)
references
References 21 publications
0
53
0
1
Order By: Relevance
“…They can be folded and tapered for more compact size and wider bandwidth [8] leading to configuration similar to the tapering U-shaped half-wavelength dipole structure [9] that is used in one of the wireless sensor modules, presented in Fig. 3, due to its compactness capability to allow for the placement of circuit components in close proximity.…”
Section: Antennas For Rfid and Sensor Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be folded and tapered for more compact size and wider bandwidth [8] leading to configuration similar to the tapering U-shaped half-wavelength dipole structure [9] that is used in one of the wireless sensor modules, presented in Fig. 3, due to its compactness capability to allow for the placement of circuit components in close proximity.…”
Section: Antennas For Rfid and Sensor Integrationmentioning
confidence: 99%
“…À111 dBm) [19], [20] while keeping clear the first Fresnel zone [9]. An RFID reader with an antenna of 6-dBi gain was used to measure this range [18].…”
Section: Lakafosis Et Al: Progress Towards the First Wireless Sensormentioning
confidence: 99%
“…Two major challenges for such applications are the choice of the materials and advanced module-level integration capabilities. Previous research has demonstrated the successful development of fully inkjet-printed RFID modules on paper [50]- [51]. Still, most of these efforts lack a discussion of the challenges involved in the integration of practical sensors on these low-cost substrate RFID tags.…”
Section: A Success Story: Ink-jet Printed Cnts In the Uhf Range For Rmentioning
confidence: 99%
“…Driven by the increasing demands for low-cost, flexible, and environment-friendly RFID systems, paper, as one of the best and cheapest organicsubstrate candidates, attracts more and more attention of researchers [1] [2]. Compared with other substrates such as FR4, paper has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other substrates such as FR4, paper has several advantages. It is biodegradable and could undergo high-efficiency reel-to-reel process, which means it can be used for mass production at low-cost [1]. Inkjet printing, as an efficient direct-write printing method, can be used to print electronics on paper substrates [2].…”
Section: Introductionmentioning
confidence: 99%